The effects of rising labour costs in the host country on MNEs' FDI decision - Kettunen, Katri (My University, 2025)
Foreign direct investment (FDI) is an important means for companies to gain competitive advantage and internationalise their operations. Many companies rely heavily on the exploitation of low labour costs when it comes to FDI. Low labour costs overall have been a major factor affecting companies’ FDI decisions. As some major host countries for FDI, such as China, have seen a shift in labour costs and availability of cheap labour, companies have needed to react. Although low labour costs have been studied as an antecedent for FDI, the effect of the rise in labour costs is substantially less studied, hence the rationale behind the choice of topic for this bachelor’s thesis. The thesis aims to answer the main research question: “What is the impact of rising labour costs in the host country on FDI decisions?” through a literature review. To aid in answering the main research questions, the thesis also inspects three sub-questions: what are the motives driving FDI decisions, what are the advantages of FDIs that affect MNEs’ decision-making process and what is the effect of labour costs on FDI? The findings show that the rise in labour costs does affect MNE’s FDI decisions, but certain industries, including manufacturing, are more susceptible to the diminishing availability of low labour in some countries. Though a common reaction to the rise in labour costs is to relocate, other possible solutions to the now lost advantage is to disperse operations, encourage technological innovation or to exit altogether.

Suorat ulkomaaninvestoinnit ovat tärkeä keino yrityksille saada kilpailuetua ja kansainvälistyä. Monet yritykset hyödyntävät matalan työvoimakustannusten maita ulkomaaninvestoinneissaan. Kun jotkut tärkeät ulkomaaninvestointien isäntämaat, kuten Kiina, ovat kokeneet muutoksen työvoimakustannuksissaan, yritykset ovat joutuneet reagoimaan. Vaikka matalia työvoimakustannuksia on tutkittu vaikuttajana yritysten ulkomaaninvestointipäätöksiin, nousevien työvoimakustannusten vaikutusta on tutkittu merkittävästi vähemmän. Tämä kandidaatintutkielma pyrkii vastaamaan päätutkimuskysymykseen: Mikä on isäntämaan nousevien työvoimakustannusten vaikutus yritysten suoriin ulkomaaninvestointipäätöksiin? Aihetta tutkitaan kirjallisuuskatsauksen avulla. Tutkielman alakysymyksinä ovat: mitkä motiivit vaikuttavat suorien ulkomaaninvestointien päätöksiin, mitä ovat suorien ulkomaaninvestointien hyödyt, jotka vaikuttavat yritysten päätöksiin ja mikä on työvoimakustannusten merkitys suorissa ulkomaaninvestoinneissa? Nämä kolme alakysymystä auttavat vastaamaan päätutkimuskysymykseen. Tutkielman löydökset osoittavat, että työvoimakustannusten nousu vaikuttaa yritysten suorien ulkomaaninvestointipäätöksiin. Tietyt toimialat ovat enemmän herkkiä työvoimakustannusten muutoksiin ja halvan työvoiman vähenemiseen. Yleinen reaktio työvoimakustannusten nousuun on siirtää sijaintia, mutta yritykset voivat myös levittäytyä useampaan sijaintiin, edistää teknologista innovaatiota tai poistua maasta kokonaan.
Keywords: labour cost, rising labour costs, foreign direct investment (FDI), OLI paradigm, motives, työvoimakustannukset, nousevat työvoimakustannukset, suora ulkomaaninvestointi, OLI paradigma, motiivit